Factor-GMM estimation with large sets of possibly weak instruments - George Kapetanios; Massimiliano Marcellino (Queen Mary University of London, Department of Economics, 2006)
This paper analyses the use of factor analysis for instrumental variable estimation when the number of instruments tends to infinity. We consider cases where the unobserved factors are the optimal instruments but also cases where the factors are not necessarily the optimal instruments but can provide a summary of a large set of instruments. Further, the situation where many weak instruments exist is also considered in the context of factor models. Theoretical results, simulation experiments and empirical applications highlight the relevance and simplicity of Factor-GMM estimation.
Keywords: C32; C51; E52; 330; Factor models; Principal components; Instrumental variables; GMM; Weak instruments; DSGE models; Sch\~AƒÂtztheorie; Momentenmethode; Dynamisches Gleichgewicht